NILAI - NILAI KEARIFAN LOKAL MASYARAKAT BALI DALAM MENJAGA KERUKUNAN BERAGAMA - Ni Luh Gede Hadriani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Indonesia is well known as a complex country which comprises wide diversity of culture such as, tribe, language, religion, and customs. This diversity should be maintained to avoid conflict, because nowadays there are some conflict which caused by religion matters. In order to solve this problem, government has done countless way. However, this religion matters still arise in several area. Yet, this condition cannot be ignored and a solution should be found. At least we still have local cultures that grow among the people of Indonesia. Beneath our local culture there are some pearls that we can find, which could give us a contribution to avoid violence in the name of religion and to develop a harmony between religion in our beloved country.